KRITIK SOSIAL DALAM LIRIK LAGU DURMAGATI DADI MENTRI KARYA KAJAWI: ANALISIS WACANA KRITIS VAN DIJK - Suwono; Hari Windu Asrini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the construction of social criticism discourse in the song lyrics "Durmagati Dadi Mentri" by Kajawi using Teun A. Van Dijk's critical discourse analysis framework. A descriptive qualitative approach was employed, with listening and note-taking techniques as data collection instruments. Analysis was conducted across three dimensions: text structure, social cognition, and social context. Findings reveal that at the text structure dimension, discourse is constructed through an accumulatively built theme of bureaucratic moral degradation, an organized ironic narrative schema, and stylistic strategies comprising krama-ngoko register contrast alongside irony-based rhetorical devices. At the social cognition dimension, the creator manifests critical awareness of systemic leadership failure while grounding his creation in Javanese cultural values as a moral foundation. At the social context dimension, the song functions as an instrument of resistance against unequal access to public discourse amid escalating post-reform political distrust. It is concluded that these lyrics constitute a cultural artifact of high ideological density and significant socio-political relevance.